Going political – multimodal metaphor framings on a cover of the sports newspaper A Bola - Almeida, Maria Clotilde (Scripta, 2016)
This paper analyses a political-oriented multimodal metaphor on a cover of the sports newspaper A Bola, sequencing another study on multimodal metaphors deployed on the covers of the very same sports newspaper pertaining to the 2014 Football World Cup in Brazil (Almeida/Sousa, 2015) in the light of Forceville (2009, 2012). The fact that European politics is mapped onto football in multimodal metaphors on this sports newspaper cover draws on the interplay of conceptual metaphors, respectively in the visual mode and in the written mode. Furthermore, there is a relevant time-bound leitmotif which motivates the mapping of politics onto football in the sports newspaper A Bola, namely the upcoming football match between Portugal and Germany. In the multimodal framing of the story line under analysis. The visual mode apparently assumes preponderance, since a picture of Angela Merkel, a prominent leader of EU, is clearly overshadowed by a large picture of Cristiano Ronaldo, the captain of the Portuguese National Football team. However, the visual modality of Cristiano Ronaldo’s dominance over Angela Merkel is intertwined with the powerful metaphorical headline “Vamos expulsar a Alemanha do Euro” (“Let’s kick Germany out of the European Championship”), intended to boost the courage of the Portuguese national football team: “Go Portugal – you can win this time!”. Thus, differently from multimodal metaphors on other covers of the same newspaper, the visual modality in this case cannot be considered the dominant factor in multimodal meaning creation in this politically-oriented layout.